Variabel Mediasi Struktur Modal, Kebijakan Dividen, dan Keputusan Investasi Pada Nilai Perusahaan Terhadap IHSG - Asriana, Tuning; Novalita, Novalita; Sari, Meita Sekar (Akuisisi : Jurnal Akuntansi, 2024)
The population in this study is the Company of Subsector Retailing Listed on the Indonesia Stock Exchange (IDX) 2019-2022 period, which includes about 28 companies. The purposive sampling technique is the sampling method used in this study, and 10 companies were obtained. Path analysis is the data analysis method used in this study with the SPSS 23 version. The result showed that company value does not have a significant effect on capital structure, company value has a negative effect on dividend policy, company value has an effect on investment decisions, company value has an effect on the composite stock price index, capital structure has an effect on the composite stock price index, dividend policy has no effect on the composite stock price index, investment decisions have an effect on the composite stock price index, and capital structure, dividend policy, and investment decisions as mediating variables are not able to mediate the effect of company value on the composite stock price index